Role of Social Capital, HR Competence, Financial Inclusion, and Financial Literacy in the Sustainable Performance of MSMEs - Fiqih Maria Rabiatul Hariroh; Pupung Purnamasari; Filda Rahmiati; Tsamrotul Jannah; Muhammad Kosim (Journal of Enterprise and Development (JED), 2026)
Purpose: This study examines the factors influencing the sustainable performance of Micro, Small, and Medium Enterprises (MSMEs) by focusing on the interaction between social capital, human resource (HR) competence, financial inclusion, and financial literacy.Method: This study adopted quantitative research design, collected data from 207 MSME actors in Bekasi Regency through structured questionnaires, and evaluated the proposed conceptual model using Structural Equation Modeling (SEM) in SmartPLS 4.0.Result: The analysis reveals that social capital, HR competence, and financial inclusion significantly impact sustainable performance. Furthermore, the study demonstrates that financial inclusion positively affects the financial literacy of MSME owners. In addition, financial literacy was found to serve as an essential mediator, strengthening the relationship between financial inclusion and the sustainable performance of MSMEs.Practical Implications for Economic Growth and Development: This research contributes to economic development by providing insights into the mechanisms that can help MSMEs transition from subsistence-level operations to sustainable, export-ready entities. By aligning financial access with capacity-building initiatives, local economies can mitigate business failure rates, promote more inclusive wealth distribution, and enhance regional competitiveness in the global market.Originality/Value: This study adds financial literacy as a mediating variable between financial inclusion and sustainable performance. Additionally, it offers an exploration of how social capital and human capital contribute to fostering sustainable MSME performance.